2007
DOI: 10.1007/s10802-007-9179-3
|View full text |Cite
|
Sign up to set email alerts
|

Forms of Aggression and Peer Victimization During Early Childhood: A Short-term Longitudinal Study

Abstract: A multi-informant and multi-measure short-term longitudinal study of the association between subtypes of aggression and peer victimization was conducted in an early childhood sample (M = 44.36 months; SD = 11.07; N = 120). Observational and teacher report measures demonstrated appropriate reliability and validity as well as stability across an academic year. Concurrent associations revealed that observed relational aggression was uniquely associated with teacher reported relational victimization and observed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
174
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(207 citation statements)
references
References 47 publications
26
174
1
6
Order By: Relevance
“…One of the remarkable aspects in the explanation of this finding seems to be the greater presence of physical aggressiveness shown by boys, which increases the likelihood of rejection by their peers (Archer, 2004;Bettencourt & Miller, 1996;Eagly & Steffen, 1986). Relational aggressiveness, in contrast, has been reported as being more likely in girls (Bjorkqvist & Niemela, 1992;Crick, Casas, & Mosher, 1997;Lagerspetz, Bjorkqvist, & Peltonen, 1988;Ostrov & Crick, 2007), although Salmivalli & Kaukiainen (2004) have also observed high levels of this aggressiveness in boys. In any case, there is a greater amount of data for physical aggressiveness in childhood, while relational aggressiveness is more frequent in adolescence (Prinstein, Boergers & Vernberg, 2001), anales de psicología, 2014, vol.…”
Section: Discussionmentioning
confidence: 99%
“…One of the remarkable aspects in the explanation of this finding seems to be the greater presence of physical aggressiveness shown by boys, which increases the likelihood of rejection by their peers (Archer, 2004;Bettencourt & Miller, 1996;Eagly & Steffen, 1986). Relational aggressiveness, in contrast, has been reported as being more likely in girls (Bjorkqvist & Niemela, 1992;Crick, Casas, & Mosher, 1997;Lagerspetz, Bjorkqvist, & Peltonen, 1988;Ostrov & Crick, 2007), although Salmivalli & Kaukiainen (2004) have also observed high levels of this aggressiveness in boys. In any case, there is a greater amount of data for physical aggressiveness in childhood, while relational aggressiveness is more frequent in adolescence (Prinstein, Boergers & Vernberg, 2001), anales de psicología, 2014, vol.…”
Section: Discussionmentioning
confidence: 99%
“…That is, direct paths are hypothesized from aggression to peer victimization, and indirect pathways are hypothesized via peer rejection. Evidence for this model has been growing in recent years (Boivin et al, 2001;Ostrov, 2008;Ostrov & Godleski, 2013). For example, in this special issue, Godleski and colleagues documented that peer rejection was associated with increases in relational victimization in early childhood, whereas low levels of emotion regulation are associated with increases in physical victimization .…”
Section: What Do We Currently Know?mentioning
confidence: 99%
“…For example, in a sample of detained adolescent girls, Marsee and Frick (2007) found that reactive relational aggression was more strongly associated with poorly regulated emotion and anger, whereas proactive relational aggression was more strongly associated with CU traits and positive outcome expectations for aggression. Additionally, Ostrov and Crick (2007) found that proactive relational aggression predicted social maladjustment (i.e., peer rejection and student-teacher conflict) in preschoolers even after controlling for reactive relational and proactive overt aggression. Reactive relational aggression also predicted student-teacher conflict controlling for reactive overt aggression.…”
mentioning
confidence: 91%